2010
DOI: 10.2108/zsj.27.746
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pleistocene Refugia on the Evolutionary History of the Japanese Hare, Lepus brachyurus

Abstract: We performed a phylogeographic analysis of the Japanese hare, Lepus brachyurus, using the mitochondrial cytochrome b gene (1140 bp). In total, 119 haplotypes were recovered from 197 samples isolated from 82 localities on three main islands of the Japanese archipelago: Honshu, Sikoku, Kyushu, Sado Island and the Oki Islands. Results showed two distinct clades at a genetic distance of 3.5%, equivalent to an estimated 1.2 million years. The two clades, encompassing seven subclades, showed an apparent geographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The divergence of these lineages was estimated to have occurred ~700,000 years ago, and sublineages B1 and B2 were estimated to have diverged ~400,000 years ago; both estimated times are in the middle Pleistocene (Figure ). Genetic differentiation between northeastern and southwestern lineages has been reported in several common animal species found across Honshu, Shikoku, and Kyushu, such as the Japanese sika deer ( Cervus nippon ), Japanese hare ( Lepus brachyurus ), tree frog ( Hyla japonica ), Pelophylax frog ( Pelophylax nigromaculatus ), and seed parasitic weevil ( Curculio hilgendorfi ) (Aoki, Kato, & Murakami, ; Dufresnes et al, ; Nagata et al, ; Nunome, Torii, Matsuki, Kinoshita, & Suzuki, ). The existence of two lineages in the aforementioned animal species was proposed based on intraspecific phylogenetic analyses, and it was tentatively explained by two biogeographical events: (a) independent migration of the two lineages from the Asian continent to Japan and (b) the expansion from northern and southern refugia within the Japanese archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…The divergence of these lineages was estimated to have occurred ~700,000 years ago, and sublineages B1 and B2 were estimated to have diverged ~400,000 years ago; both estimated times are in the middle Pleistocene (Figure ). Genetic differentiation between northeastern and southwestern lineages has been reported in several common animal species found across Honshu, Shikoku, and Kyushu, such as the Japanese sika deer ( Cervus nippon ), Japanese hare ( Lepus brachyurus ), tree frog ( Hyla japonica ), Pelophylax frog ( Pelophylax nigromaculatus ), and seed parasitic weevil ( Curculio hilgendorfi ) (Aoki, Kato, & Murakami, ; Dufresnes et al, ; Nagata et al, ; Nunome, Torii, Matsuki, Kinoshita, & Suzuki, ). The existence of two lineages in the aforementioned animal species was proposed based on intraspecific phylogenetic analyses, and it was tentatively explained by two biogeographical events: (a) independent migration of the two lineages from the Asian continent to Japan and (b) the expansion from northern and southern refugia within the Japanese archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…In Japanese beech, F. crenata, the Clade III chloroplast DNA haplotype that occurs in Kyushu, the western half of Chugoku District, and Shikoku is substituted by Clade II in the Kii Peninsula (Fujii et al 2002). Furthermore, recent phylogeographical analyses of mammals such as the Japanese monkey Macaca fuscata and Japanese deer Cervus nippon have also shown that there are separate mitochondrial clades between Shikoku and the Kii Peninsula (Kawamoto 2007, Nunome et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the age of the most recent common ancestors (TMRCAs) for mtDNA clades using the Cytb sequences and a relaxed Bayesian molecular clock with uncorrelated rates (Bayesian evolutionary analysis by sampling trees (BEAST) v1.6.1, Drummond and Rambaut, 2007), as described previously (Nunome et al, 2010b). For this analysis, we used M. cypriacus, M. macedonicus, M. spicilegus and M. spretus, the remaining members of the M. musculus Species Group, as outgroup taxa.…”
Section: Phylogeny and Divergence Time Estimationmentioning
confidence: 99%